Shaping Higher Education with Students - ways to connect Research and Teaching - Sotiriou, Mina; C.H. Tong, Vincent; Standen, Alex (UCL Press, 2018)
Forging closer links between university research and teaching has become an important way to enhance the quality of higher education across the world. As student engagement takes centre stage in academic life, how can academics and university leaders engage with their students to connect research and teaching more effectively? In this highly accessible book, the contributors show how students and academics can work in partnership to shape research-based education. Featuring student perspectives, it offers academics and university leaders practical suggestions and inspiring ideas on higher education pedagogy, including principles of working with students as partners in higher education, connecting students with real-world outputs, transcending disciplinary boundaries in student research activities, connecting students with the workplace, and innovative assessment and teaching practices. Written and edited in full collaboration with students and leading educator-researchers from a wide spectrum of academic disciplines, this book poses fundamental questions about learning and learning communities in contemporary higher education.